Spinal mobilization force-time characteristics: A scoping literature review. - Lindsay M Gorrell MChiroprac; Luana Nyirö; Mégane Pasquier; Isabelle Pagé; Nicola R Heneghan; Petra Schweinhardt; Martin Descarreaux (PLoS ONE)
Background Spinal mobilization (SMob) is often included in the conservative management of spinal pain conditions as a recommended and effective treatment. While some studies quantify the biomechanical (kinetic) parameters of SMob, interpretation of findings is difficult due to poor reporting of methodological details. The aim of this study was to synthesise the literature describing force-time characteristics of manually applied SMob. Methods This study is reported in accordance with the Preferred Reporting Items for Scoping Reviews (PRISMA-ScR) statement. Databases were searched from inception to October 2022: MEDLINE (Ovid), Embase, CINAHL, ICL, PEDro and Cochrane Library. Data were extracted and reported descriptively for the following domains: general study characteristics, number of and characteristics of individuals who delivered/received SMob, region treated, equipment used and force-time characteristics of SMob. Results There were 7,607 records identified and of these, 36 (0.5%) were included in the analysis. SMob was delivered to the cervical spine in 13 (36.1%), the thoracic spine in 3 (8.3%) and the lumbopelvic spine in 18 (50.0%) studies. In 2 (5.6%) studies, spinal region was not specified. For SMob applied to all spinal regions, force-time characteristics were: peak force (0-128N); duration (10-120s); frequency (0.1-4.5Hz); and force amplitude (1-102N). Conclusions This study reports considerable variability of the force-time characteristics of SMob. In studies reporting force-time characteristics, SMob was most frequently delivered to the lumbar and cervical spine of humans and most commonly peak force was reported. Future studies should focus on the detailed reporting of force-time characteristics to facilitate the investigation of clinical dose-response effects.